Accounting Practices of Travelers’ Income based on Local Wisdom Values: An Islamic Ethnomethodology Study - Thalib, Mohamad Anwar; Roni Mohamad (Institut Agama Islam Negeri Ponorogo, 2025)
Abstract: Introduction/Main Objectives: This study aims to explore the income accounting practices of travelers from Gorontalo to Mecca using bicycles, focusing on the integration of local wisdom values. It seeks to understand how these travelers manage their income in alignment with Islamic teachings. Background Problems: Despite extensive research on accounting practices, there is limited exploration of how travelers apply local wisdom in income management during religious journeys. This study addresses this gap by investigating how travelers generate and document their income. Novelty: This study introduces an Islamic ethnomethodological approach to examining income accounting practices, highlighting the role of gratitude and cultural values in financial management, an aspect not widely explored in previous research. Research Methods: The study adopts a qualitative research method using structured interviews. Data analysis follows five stages: charity, knowledge, faith, revelation information, and courtesy. Findings/Results: The findings reveal various income accounting practices, including revenue sources from selling t-shirts, recording income based on memory, and price differentiation between Indonesia and Singapore to optimize earnings. These practices reflect a deep sense of gratitude toward the Creator. In Gorontalo’s Islamic culture, gratitude is expressed through the proverb